PERLINDUNGAN HUKUM BAGI PEMEGANG MEREK TERDAFTAR JASA WARUNG KOPI DI KOTA KENDARI - Ismail Salam; Muhammad Fitriadi; Suriani BT Tolo (Universitas Muhammadiyah Mataram, 2021)
The existence of problems with registered trademarks of coffee shop services in various regions in Indonesia, does not mean that in Kendari City, which has many coffee shop service businesses, it will be spared from piracy of registered trademarks of coffee shop services. Therefore, this study aims to determine the form of legal protection for registered trademark holders of coffee shop services in Kendari City. The type of research used is normative-empirical legal research, with a theoretical approach. While the legal materials used are primary legal materials from library research and secondary legal materials from field research. Then the two legal materials were analyzed qualitatively. The results show that in the business world or the business world, registered trademarks in coffee shop business services are exclusive intellectual property rights. The owners are given legal protection both preventively and repressively as regulated in Law no. 20 of 2016. If there are other parties who hijack a registered coffee shop service mark with bad ethics, then the